2021
DOI: 10.1136/bmjpo-2020-000861
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of serious bacterial infections using serum biomarkers in an infant population aged 0 to 90 days: a prospective cohort study

Abstract: ObjectiveYoung febrile infants represent a vulnerable population at risk for serious bacterial infections (SBI). We aimed to evaluate the diagnostic accuracy of components of the complete blood count in comparison with C-reactive protein (CRP) to predict SBI among febrile infants.Design and settingProspective cohort study conducted in a tertiary emergency department between December 2018 and November 2019.PatientsWe included febrile infants ≤3 months old with complete blood count results. We analysed their whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…10,18,19 We found that CRP and PCT as single biomarkers were strong predictors of SBIs and IBIs. In line with the findings of previous studies, 6,20,21 CRP ≥20mg/L performed best in predicting SBIs with an AUC of 0.741.…”
Section: Discussionsupporting
confidence: 90%
“…10,18,19 We found that CRP and PCT as single biomarkers were strong predictors of SBIs and IBIs. In line with the findings of previous studies, 6,20,21 CRP ≥20mg/L performed best in predicting SBIs with an AUC of 0.741.…”
Section: Discussionsupporting
confidence: 90%
“…Its physiological levels have been widely studied, even within the initial hours of life [ 62 ]. Compared to white blood cell count (WBC), absolute neutrophil count (ANC), and neutrophil-to-lymphocyte ratio (NLR), CRP exhibits superior discriminatory performance for SBI in the context of young infants presenting with fever in the ED, as evidenced by an area under the receiver operator curve (ROC) of 0.815 (95% confidence interval (CI) 0.748 to 0.883) [ 63 ]. It is crucial to emphasize that none of these individual biomarkers achieve perfection, aligning with findings from prior studies.…”
Section: From Biomarkers To Safety Nets: An Exploration Of Potential ...mentioning
confidence: 99%
“…Organisms present in the mother can be passed to the fetus by blood, rectovaginal, amniotic fluid and placenta, causing neonate PM (9). Some hematology tests, such as white blood cell (WBC), C-reactive protein (CRP), and procalcitonin (PCT) tests, are of limited value individually due to their low sensitivity and cannot be used to predict PM (10).…”
Section: Introductionmentioning
confidence: 99%